A Journey, Not a Destination - James L. Phelps (Educational Considerations, 2011)
Closing Essay: Much of the motivation and ideas for the articles in this special issue originated with my dear friend, Maris Abolins, Professor Emeritus of Physics at Michigan State University. We started as neighbors and, as our kids grew up together, we socialized frequently. He is responsible for my interest in physics. I would read a physics book, which would become the subject of our next dinner conversation (while our wives talked about other, more social topics). Instead of a compilation of facts, physics became a way of thinking about problem solving. The “unified field” theory was the start of my new thinking.
Keywords: Destination; Albert Einstein; solutions; mathematical; economics; literature; education; research; achievement; principles; consistency; measurement; planning; journey